Pengaruh Capital Intensity Dan Leverage Terhadap Tax Avoidance Pada Perusahaan Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Pada Tahun 2019-2021 - Evelyn Tio Rizki Hutabarat; Anik Yuliati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine and analyze the effect of capital intensity, profitability, and leverage on tax avoidance in companies listed on the Indonesia Stock Exchange in the property and real estate sector during 2019-2021. The research method used is quantitative and uses research variables including